Prognostic Value of Normal Stress Echocardiography in Obese Patients - Michele Murphy; Siva Krothapalli; Jose Cuellar; Somsupha Kanjanauthai; Brian Heeke; Pallavi S. Gomadam; Avirup Guha; Vernon A. Barnes; Sheldon E. Litwin; Gyanendra K. Sharma (Hindawi Limited, 2014)
Background. Chest pain is a common problem in obese patients. Because of the body habitus, the results of noninvasive evaluation for CAD may be limited in this group. Methods. We reviewed the records of 1446 consecutive patients who had undergone clinically indicated stress echocardiography (SE). We compared major adverse cardiac events (MACE; myocardial infarction, cardiac intervention, cardiac death, subsequent hospitalization for cardiac events, and emergency department visits) at 1 year in normal weight, overweight, and obese subjects with normal SE. Results. Excluding patients with an abnormal and indeterminate SE and those who were lost to follow-up, a retrospective analysis of 704 patients was performed. There were 366 obese patients (BMI ≥ 30), 196 overweight patients (BMI 25-29.9), and 142 patients with normal BMI (18.5-24.9). There was no MACE in the groups at 1-year follow-up after a normal SE. Conclusions. In obese patients including those with multiple risk factors and symptoms concerning for cardiac ischemia, stress echocardiography is an effective and reliable noninvasive tool for identifying those with a low 1-year risk of cardiac events.